2015
DOI: 10.18632/oncotarget.3846
|View full text |Cite
|
Sign up to set email alerts
|

ATRX represses alternative lengthening of telomeres

Abstract: The unlimited proliferation of cancer cells requires a mechanism to prevent telomere shortening. Alternative Lengthening of Telomeres (ALT) is an homologous recombination-mediated mechanism of telomere elongation used in tumors, including osteosarcomas, soft tissue sarcoma subtypes, and glial brain tumors. Mutations in the ATRX/DAXX chromatin remodeling complex have been reported in tumors and cell lines that use the ALT mechanism, suggesting that ATRX may be an ALT repressor. We show here that knockout or kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
142
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 41 publications
9
142
1
2
Order By: Relevance
“…DAXX and ATRX are both important for homologous recombination by impairing the heterochromatic state of telomeres . It has been shown that ATRX expression represses ALT activity and in human cancer loss of ATRX is reported as another ALT feature . We found a loss of ATRX expression in all ALT‐positive canine tumor samples whereas all but two other analyzed ALT‐negative tumors did express ATRX.…”
Section: Discussionmentioning
confidence: 59%
“…DAXX and ATRX are both important for homologous recombination by impairing the heterochromatic state of telomeres . It has been shown that ATRX expression represses ALT activity and in human cancer loss of ATRX is reported as another ALT feature . We found a loss of ATRX expression in all ALT‐positive canine tumor samples whereas all but two other analyzed ALT‐negative tumors did express ATRX.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, the current understanding is that ATRX mutations rather provoke ALT, but additional genetic or epigenetic changes are probably required to activate the ALT pathway fully . Nevertheless, it has been shown recently that transient restoration of ATRX expression repressed the ALT phenotype in ALT‐positive/ATRX negative cells of mesenchymal origin . Thus, further studies are needed to uncover comprehensively the underlying molecular mechanisms leading to ALT in tumours lacking nuclear ATRX expression.…”
Section: Discussionmentioning
confidence: 99%
“…A strong candidate is the histone chaperone ATRX, which is mutated in a large majority of cells and tumours that exploit the ALT pathway 110,111 . Reintroducing ATRX into ALT cells suppresses T-SCE, APB and c-circle formation, and inter-chromosomal telomeric recombination 112,113 (FIG. 3c).…”
Section: Peeling Back Layers Of End Protectionmentioning
confidence: 99%
“…Taken together, these studies suggest that both the helicase-unwinding activity of ATRX and the histone chaperone properties of the ATRX–DAXX complex are likely to counteract telomere recombination by resolving stable secondary structures that would otherwise impede fork progression. It is important to emphasize that ATRX depletion by itself is not sufficient to induce ALT 112,113 , indicating that additional genetic alteration(s) are necessary. Interestingly, deletion of the gene encoding the histone chaperone ASF1A is sufficient to trigger ALT-like phenotypes in telomerase-positive cells 120 , and binding of the nucleosome-remodelling deacetylase (NuRD) complex to variant repeats found at telomeres in ALT cells creates a permissive environment for recombination 121 .…”
Section: Peeling Back Layers Of End Protectionmentioning
confidence: 99%